1995
DOI: 10.1063/1.114562
|View full text |Cite
|
Sign up to set email alerts
|

High critical-current density of Nd(Ba,Nd)2Cu3O7−δ single crystals

Abstract: We have studied the superconducting properties of Nd(Ba1−xNdx)2Cu3O7−δ (Nd123, x≊0.1) single crystals grown by the traveling-solvent floating-zone method under 0.1% O2 in Ar atmosphere. An anomalous peak effect in the magnetization hysteresis (M–B) loop is observed in the Nd123 single crystals as well as in the Nd123 bulk crystals prepared by the oxygen-controlled melt growth (OCMG) method. The critical current density (Jc) of the Nd123 single crystals is 70 600 A/cm2 in 1.0 T at 77 K for the applied field per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(62 citation statements)
references
References 9 publications
1
61
0
Order By: Relevance
“…Analogous to the SRL-CP method, the employment of Ba-rich precursors in TSMG process have been also reported [8]. In all cases, finely dispersed Nd 1+x Ba 2-x Cu 3 O 7-y grains with different x ,which work as field induced pinning centers, have been observed in the superconducting matrices [9]. As a result, field dependence of J c measurements show J c peaks at intermediate fields [10].…”
Section: -1 Phase Diagrammentioning
confidence: 83%
“…Analogous to the SRL-CP method, the employment of Ba-rich precursors in TSMG process have been also reported [8]. In all cases, finely dispersed Nd 1+x Ba 2-x Cu 3 O 7-y grains with different x ,which work as field induced pinning centers, have been observed in the superconducting matrices [9]. As a result, field dependence of J c measurements show J c peaks at intermediate fields [10].…”
Section: -1 Phase Diagrammentioning
confidence: 83%
“…Y123 single crystals with newly discovered point-defect-type pinning sites [5], which were introduced by substituting impurity ions with low concentration to the specific sites, are also examined. According to the transmission electron microscope study, it was revealed that these substituted ions did not form the large clusters such as RE/Ba substitutions [6,7], suggesting that the volume of pinning sites by these impurities is much smaller than that of the RE-rich local regions with typical size of several ten nm as reported several literatures. Their J c -H-T properties were discussed from the viewpoint of the difference in the spatial size of these pinning sites.…”
Section: Introductionmentioning
confidence: 82%
“…Therefore the temperature dependence of the f p for these pinning sites were considered from viewpoint of the different spatial size. Since the Gd/Ba substituted region has the typical size of several ten nm in the ab-plane [6,7], which is much larger than the coherence length, ξ ab , the difference in the condensation energy between the superconducting matrix and the Gd/Ba substituted region should give the pinning energy. Thus the f p for Gd/Ba substituted region is expressed in the framework of textbooks; f p, Gd/Ba ≈…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Among such compounds, NdBa 2 Cu 3 O y (Nd-123) is the most promising because of its high superconducting transition temperature and enhanced critical current density. [5][6][7] Contrary to YBa 2 Cu 3 O y (Y-123), the Nd 1+x Ba 2-x Cu 3 O y phase reveals a region of homogeneity, and the superconducting properties of the material deteriorate sharply when barium is replaced by neodymium. [8] The region of homogeneity stretches from x = 0 to x = 1 in the Nd 1+x Ba 2-x Cu 3 O y solid solution.…”
Section: Introductionmentioning
confidence: 93%